Physical workload and posture on pine nut collection in Santa Catarina Carga de trabalho físico e postura na coleta de pinhão na região serrana de Santa Catarina - de Britto P.C. (2018)
© 2018 Fundacao de Pesquisas Florestais do Parana.The collection of pine nut, or seeds of Araucaria angustifolia, represents an important income source for farm families in Southern Brazilian regions. Pinning is a technique used after the pinion closure period as determined by the DC/Ibama n.20/76 regulation. On the pinning process, rural workers climb trees by using auxiliary equipment. In this context, this research aimed to analyze the physical workload and posture adopted by workers in pine nut collection to improve the comfort conditions, health and safety. The data were collected on farms in the mountainous region of Santa Catarina State, Brazil. The physical workload was obtained by monitoring heart rate of workers at work by using the monitor Polar Oy, and the work was classified according to the methodology proposed by Apud (1989). The assessment of posture was taken by filming the workers, and the data were submitted for analysis in the analysis of postures "WinOwas" software. The results showed that the clibbing and clib down of the trees were the work phases more physically demanding and that caused greater strain on workers due to the high risk of accidents. The work is classified as moderately heavy physical demand. The approach proved inadequate in the stages of overthrow and grooming of the cones. The adoption of ergonomic measures to improve working conditions is recommended.